Effect of life style (exercise and nutrition) on occurrence of breast cancer in women: A retrospective study in Babylon governorate - Hassan, Najat Hamza; Ali, Rabea M (Journal of Contemporary Medical Sciences, 2015)
Objective To identify the effect of exercise and nutrition on breast cancer occurrence and to find the relationship between life style and some demographic and reproductive variables. Methods A retrospective study (case control study) of a purposive sample of 400 women; 200 women diagnosed with breast cancer visited the Merjan Teaching Hospital Oncology Cancer Center in Babylon Governorate as a study group and 200 women free of breast cancer as a control group. An assessment tool was constructed for the purpose of the study. It comprised of socio-demographic data, reproductive data, information related to breast cancer (stage, side, period, family history) and information related to their life style: exercise (5 items) and nutrition (14 items) of 10 years previous breast cancer occurrence, physical measurements for measuring obesity and overweight (BMI) as well as medical records to explain in the stage of breast cancer and other details which may be assisting this study Data were collected from 4 May 2013 to 4 July 2013. Analysis of data was performed through the application of descriptive and inferential statistical data analysis approach. Results The study demonstrates that the highest percentage (39.5%) of study sample was in age group 50–54 years in comparison with the other age groups for both the study and control groups. There was a high significant difference at P < 0.01 between the life aspects (exercise and nutrition) and breast cancer in women while no relationship between life aspects and demographical and reproductive variables except with interval between pregnancies and duration of contraception of study group was noted. Conclusion Establishing an activation media and Ministry of Health role for guiding women and their families about the importance of exercise and healthy nutrition which contributes to reducing the incidence of breast cancer occurrence and the importance of early detection of breast cancer.